Creepy but Inevitable?: The Evolution of Social Networking - Zhang, Hui; Choudhury, Munmun De; Grudin, Jonathan (CSCW '14 Proceedings of the 17th ACM conference on Computer Supported Cooperative Work & Social Computing, 2014)
This paper focuses on the fifth year of a cross-sectional trend study of enterprise social networking. Several stable patterns are evident—some activities have plateaued, others steadily increase in frequency. The fifth year did see a new development: As social networking companies visibly embraced behavior tracking and targeted advertising, concerns shifted from boundary regulation within personal networks to unsettling evidence of activity monitoring. However, benefits of use continue to outweigh drawbacks.